Bioactive Formulations in Agri-Food-Pharma: Source and Applications - Kandi Sridhar; Zeba Usmani; Minaxi Sharma (Bioengineering, 2023)
Bioactive compounds are the secondary metabolites produced by the plant cell through numerous metabolic pathways [...]